Utilização do Cipionato de estradiol e benzoato de estradiol em protocolos de inseminação artificial em tempo fixo em novilhas mestiças (Bos taurus indicus x Bos taurus taurus). - Sobreira, Roberto Ramos (2015)
Theefficiency of two different synchronizers and ovulation inductionwere evaluated: estradiol benzoate (EB), estradiol cypionate(EC) in artificial insemination protocols in fixed time (TAI) on the follicular dynamics and heifers pregnancy rate crossbred created in extensive farming conditions. So, 128 heiferswereusedin two runs with a completely randomized design. All animals were subjected to the same synchronization protocol: day 0 (D0), within the vaginaprogesterone insertion device (DIV) plus intramuscularly (IM) 2mg EB; day 8 (D8), withdrawal of DIV, application (IM) of 0.15mg of PGF2aand 300 IU of eCG; on 8 animals were divided into two treatments: 1) Treatment with EC on 8 -In 64 heifers was applied 1.0mgof EC IM at D8 and the AI was performed 48 hours after the removal of the DIV; 2) Treatment with EBon Day 9 -In 64heifers was applied1mg of EB in D9 IM and AI was performed 52 hours after removal of the DIP. Ten animals in each group were separated for evaluation of follicular dynamics, ultrasound examinations performed on days 0, 8, and day 10. From ultrasonograpyD10 was performed in 12 of 12 hours to determine the absence of ovulation of follicles dominant. In the remaining 108 heifers, still divided into two groups, the pregnancy rate at 30days was assessed after TAI for both protocols. Variables related to follicular dynamics were analyzed by analysis of variance (ANOVA) with the 5% level of significance, and to compare betweenovulation rate andbetween pregnant rates, in each treatment,was used the chisquare test. Of the 10 heifers evaluatedin TBE9 six did not respond to treatment because it was not verified presence of ovulatory follicle and corpus luteum. As for the number of follicles classified according to their size follicles <6 mm, 6-8 mm and <8 mm, only difference was observed (p<0.05) between treatments at day 8 for the follicles> 8 mm. No significant differences (p>0.05) for follicular growth rate are 0.81 ± 0.63mm / day and 0.89 ± 0.26 mm / day to EB and EC, respectively. There was no difference between CE and BE, to the diameter of the dominant follicle (10.97 ± 1.24 and 9.77 ± 1.36mm, respectively) and range of ovulation to TAI (13.20 ± 3.79 and 23. 00 ± 14.28h, respectively). The withdrawal of progesterone device ovulation in hours was 60.60 ± 3.69 and 74.75 ± 15.17h respectivelyfor CE and BE (p<0.05).There were differences (p<0.05) between treatments for ovulation rate, which was 90.00% and 40.00% for CE and BE, respectively.Noeffects of treatments (p>0.05) for pregnancy rate, which was 37.3% for both treatments. The TAI protocol with EC provision on 8 enables the reduction of a management in TAI protocols without influencing pregnancy rate of crossbred heifers raised on pasture